Cultural determinants and strategic priorities for medication safety in acute care: a multidisciplinary Delphi study - Neville Schembri; Hannah-Kim Grima Formosa; Kevin Holmes; Marie Clare Cassar; Shane Desselle; Timothy F Chen; Maria Cordina; Lorna Bonnici West (International Journal for Quality in Health Care, 2026)
Abstract Background Organisational culture, defined as the shared values, assumptions, and norms that influence behaviour within organisations, is widely recognised as a key determinant of patient safety in healthcare systems. Within acute care settings, medication safety represents a critical component of patient safety and depends on the ability of healthcare professionals to recognise risks, communicate openly, and intervene before errors result in patient harm. However, medication use is inherently interdisciplinary and requires effective coordination between multiple professional groups. Understanding how organisational culture influences medication safety practices across healthcare professions is therefore essential to inform governance, policy, and improvement strategies. This study aimed to achieve expert consensus on the organisational cultural factors influencing medication safety practices, barriers to medication error reporting, and strategies to strengthen medication safety in acute healthcare settings. Methods A modified electronic Delphi method was used to synthesise expert perspectives. A multidisciplinary panel of 41 healthcare professionals practising in Malta’s acute care system were invited to participate, including nurses, midwives, medical doctors, and pharmacists. In Round 1, participants completed an exploratory qualitative questionnaire consisting of three open-ended questions addressing cultural influences on medication safety, barriers to error reporting, and potential improvement strategies. Responses were analysed using inductive content analysis, generating thematic categories that informed the development of 20 structured statements grouped into four domains: organisational safety culture and psychological safety; workforce and operational pressures; reporting culture and barriers; and strategies to strengthen medication safety. In Round 2, participants rated the importance of each statement using a five-point Likert scale. Consensus was predefined as ≥ 70% agreement. Results A total of 28 out of 41 healthcare professionals participated in Round 1 (68.3% response rate), including nurses (n = 15), midwives (n = 5), medical doctors (n = 5), and pharmacists (n = 3). Round 1 identified seven categories grouped into four domains, with blame culture emerging as a key barrier to medication error reporting. In Round 2 (n = 25/41; 61.0% response rate), consensus (≥70%) was reached for all but one statement. The strongest consensus centred on psychological safety, open communication, and adequate staffing. Conclusion Findings indicate that medication safety is shaped primarily by organisational culture and systemic conditions rather than technical safeguards alone. Establishing a psychologically safe, non-punitive environment supported by engaged leadership and appropriate workforce conditions is fundamental for encouraging transparent reporting, organisational learning, and safer medication practices. These insights can inform policy development, organisational governance, and future research aimed at strengthening medication safety cultures in healthcare systems.